2008
DOI: 10.1111/j.1399-0004.2008.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in HNPCC: cumulative lifetime incidence, survival and tumour distribution. A report of 121 families with proven mutations

Abstract: Hereditary non-polyposis colorectal cancer (HNPCC) is an autosomal dominant condition caused by inactivating mutations of DNA mismatch repair (MMR) genes. An accurate estimation of colorectal cancer risk for mutation carriers is essential for counselling and rationalizing screening programmes. Families were referred on the basis of clinical criteria. Tumour immunohistochemistry and microsatellite testing were performed. Appropriate patients underwent sequencing of all relevant exons of the MMR genes. Proven an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 27 publications
(123 reference statements)
4
64
1
Order By: Relevance
“…Furthermore, neither review identified more than four studies related to LS. Between them they identified only seven separate reviews, 23,49,50,59,61,81,82 of which all but one had already been identified by our review. The one study we had not identified, by Hagen and colleagues, 82 was written in German and therefore excluded from our review.…”
Section: Summary Of Previous Cost-effectiveness Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, neither review identified more than four studies related to LS. Between them they identified only seven separate reviews, 23,49,50,59,61,81,82 of which all but one had already been identified by our review. The one study we had not identified, by Hagen and colleagues, 82 was written in German and therefore excluded from our review.…”
Section: Summary Of Previous Cost-effectiveness Reviewsmentioning
confidence: 99%
“…The one study we had not identified, by Hagen and colleagues, 82 was written in German and therefore excluded from our review. The only results presented by Antonanzas and colleagues were from the Barrow and colleagues (2008) 81 paper, which we excluded on the basis of population. The four studies 23,49,50,59 reported by Rogowski and colleagues 77 were all included in our review, which had a more comprehensive set of studies.…”
Section: Summary Of Previous Cost-effectiveness Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hereditary nonpolyposis colorectal cancer (HNPCC) syndrome is a major cause of hereditary colorectal cancer, predominantly within the proximal colon, with 50-80% cumulative life time risk in mutation carriers, and in addition female carriers are at a 40-60% risk of endometrial cancer and a 10-15% risk of ovarian cancer [5][6][7]. A number of other tumors types, i.e., gastric cancer, cancer of the small intestine and the upper urinary tract, skin tumors, brain tumors, and soft tissue sarcomas, have also been linked to HNPCC, albeit at lower frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…MSH2-mutation carriers show a higher incidence (48-61%) of extra colonic malignancies (gastric, pancreatic, small bowel, rectal, urological and ovarian cancer) when compared to MLHmutation carriers (11-42%) [13]. MLH1 and MSH2 mutation carriers have an overall higher cancer risk (44-79% and 38-78%) when compared with MSH6 and PMS2 mutation carriers; and the highest cumulative risk for CC at age 70 (50-65% and 40-65%, respectively), with a mean age of onset of 43-46 years old [14].…”
Section: Discussionmentioning
confidence: 99%